CJEU and Qualification Directive - Klimanova, Linda (Riga Graduate School of Law, 2018)
The aim of the paper is to analyse how and in what situations the Court of Justice of the European Union applies and interprets international law and what margin of appreciation it leaves for national courts when applying the Qualification Directive. The main focus is on the exploration of the strategies of the Court towards Convention and Qualification Directive in asylum cases related to terrorism and public security.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; Court of Justice of the European Union (CJEU); Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law